Hak dan Kewajiban Warga Negara dalam Hukum Islam dan Implikasinya terhadap Sistem Hukum Indonesia: Rights and Obligations of Citizens in Islamic Law and Their Implications for the Indonesian Legal System - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Afifudin Sihabul Millah; Rahmawati Ika Fitri Rosyadi; Khomahudi Nur Wahid (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Islamic law provides a comprehensive framework that regulates the rights and obligations of individuals in their relationships with God, fellow humans, and the state. The integration of Islamic law into public affairs in Indonesia, a predominantly Muslim country, presents the challenge of aligning the principles of this religion with the country's pluralistic legal framework. This research explores how Islamic legal principles regarding the rights and responsibilities of citizens interact with the Indonesian legal system, which is based on the principles of Pancasila and the national constitution. This research uses the research methodology of a legislative approach (law approach), legal cases (case approach), conceptual analysis (conceptual approach), historical perspective (historical approach), and comparative. The research results show that although there is potential conflict between Islamic law and national law, proper integration can strengthen social order and justice. This research also highlights the importance of dialogue between stakeholders to formulate legal policies that are inclusive and fair, and support the supremacy of law in Indonesia. This research provides a critical assessment of the application of Islamic law in Indonesia, especially in the context of citizenship, and proposes several solutions to overcome potential conflicts between legal systems. By highlighting real cases in several regions that strictly apply Sharia law, this research concludes that harmonization of Islamic law with the national legal system is not only important to maintain the religious identity of the majority of Indonesian society, but also to maintain the integrity of the nation in the midst of diversity.